Nonalcoholic fatty liver disease and polycystic ovary syndrome - Vassilatou, Evangeline (Baishideng Publishing Group Inc, 2014)
Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in the Western world comprising a spectrum of liver damage from fatty liver infiltration to end-stage liver disease, in patients without significant alcohol consumption. Increased prevalence of NAFLD has been reported in patients with polycystic ovary syndrome (PCOS), one of the most common endocrinopathies in premenopausal women, which has been redefined as a reproductive and metabolic disorder after the recognition of the important role of insulin resistance in the pathophysiology of the syndrome. Obesity, in particular central adiposity and insulin resistance are considered as the main factors related to NAFLD in PCOS. Moreover, existing data support that androgen excess, which is the main feature of PCOS and is interrelated to insulin resistance, may be an additional contributing factor to the development of NAFLD. Although the natural history of NAFLD remains unclear and hepatic steatosis seems to be a relatively benign condition in most patients, limited data imply that advanced stage of liver disease is possibly more frequent in obese PCOS patients with NAFLD. PCOS patients, particularly obese patients with features of the metabolic syndrome, should be submitted to screening for NAFLD comprising assessment of serum aminotransferase levels and of hepatic steatosis by abdominal ultrasound. Lifestyle modifications including diet, weight loss and exercise are the most appropriate initial therapeutic interventions for PCOS patients with NAFLD. When pharmacologic therapy is considered, metformin may be used, although currently there is no medical therapy of proven benefit for NAFLD. Long-term follow up studies are needed to clarify clinical implications and guide appropriate diagnostic evaluation, follow-up protocol and optimal treatment for PCOS patients with NAFLD.